The developing relationship between recently placed foster infants and toddlers and their foster carers: Do demographic factors, placement characteristics and biological stress markers matter?. (November 2015) - Van Andel, H.W.H.; Post, W.J.; Jansen, L.M.C.; Kamphuis, J.S.; Van der Gaag, R.J.; Knorth, E.J.; Grietens, H.
Abstract: Background: Infants and toddlers often react to a foster family placement with avoidant behavior. Foster carers may interpret this as if the child is adapting quite well to the new family. This misunderstanding may lead to stress in the child and create a risk for an enduring relationship. Objectives: To investigate the quality of newly formed relationships between recently placed infants and toddlers and their foster carers. Methods: In a sample of 123 foster families interactions between foster children, aged between 6 weeks and 42 months, and foster carers were videotaped and coded according to a semi-structured procedure (Emotional Availability Scales; EAS). Foster carers were asked to fill in a parenting stress scale (NOSI-R). Children's case files were studied for demographic and placement characteristics. Samples of children's salivary cortisol were taken. Results: 70-80 % of the children scored low on EAS responsiveness and involvement. The majority of foster carers did not perceive stress in the relation with their foster child (NOSI-R). The children who gave rise to relational stress tended to show higher levels of salivary cortisol. Conclusions: If foster carers do recognise relational stress, this may indicate stress in the child. It is important that foster carers learn to recognise this shut off behavior as a possible risk factor because it may lead to maladaptation and chronic stress in young foster children. Implications for research and practice are discussed. Highlights: The relationship between foster carer and foster child is under stress if foster carers do not act in a sensitive way. Babies and toddlers are at risk after placement because of their unique way of adapting to their new foster home. Emotional availability and parental stress are useful concepts to evaluate the relation between foster carers and child. Foster carers need to recognize shut off coping behavior in their foster child as a problem that needs attention. Foster carers need to learn to cope with the child in a more personal and secure way.